D313Y Variant in Fabry Disease: A Systematic Review and Meta-analysis. (8th November 2022) - Palaiodimou, Lina; Stefanou, Maria-Ioanna; Bakola, Eleni; Papadopoulou, Marianna; Kokotis, Panagiotis; Vrettou, Agathi-Rosa; Kapsia, Eleni; Petras, Dimitrios; Anastasakis, Aris; Xifaras, Nikolaos; Karachaliou, Eleni; Touloumi, Giota; et al.
Abstract : Background and Objectives: There is accumulating evidence in the literature indicating a strong correlation between Fabry disease (FD) phenotypes and specific sequence variations in the Galactosidase Alpha ( GLA ) gene. Among them, the potential pathogenicity and clinical relevance of D313Y variation in patients with FD remain debated. Methods: We performed a systematic review and meta-analysis of studies reporting D313Y as single occurring variant in the GLA gene and sought to evaluate (1) the prevalence of D313Y variation in different populations with or without clinical manifestations of FD, (2) the clinical FD phenotype in D313Y -positive patients, and (3) the proportion of D313Y -positive patients presenting abnormal laboratory findings (alpha-galactosidase-A deficiency or globotriaosylceramide accumulation). Results: Forty cohorts comprising 211 individuals with D313Y variation among 42, 723 participants with available GLA gene-sequencing data were included. Patients highly suspected for FD had a higher prevalence of D313Y variation (4.9%, 95% CI 1.6%–9.9%; I 2 = 95.5%) compared with the general population (0%, 95% CI 0%–0.1%; I 2 = 1.9%; p = 0.004). The prevalence of D313Y variation was 0.6% (95% CI 0.3%–1%; I 2 = 74.1%), 0.4% (95% CI 0.2%–0.7%; I 2 = 0%), and 0.3% (95% CI 0.2%–0.4%; I 2 = 0%) in patients presenting with neurologic, cardiac, or renal manifestations, respectively. D313Y was associated with a milder, late-onset FD phenotype, as indicated by the mean patient age of 51 years (95% CI 44–59; I 2 = 94%) and the evidence of alpha-galactosidase A deficiency and globotriaosylceramide accumulation in 26.7% (95% CI 15.3%–40%; I 2 = 34%) and 16.2% (95% CI 8%–26.4%; I 2 = 35%) of cases, respectively. D313Y -positive patients displayed predominantly neurologic FD manifestations (58.1%, 95% CI 37.7%–77.1%; I 2 = 78%), with central and peripheral nervous system (CNS/PNS) involvement noted in 28.2% (95% CI 15.4%–43.2%; I 2 = 51%) and 28.5% (95% CI 17.8%–40.5%; I 2 = 61%) of cases, respectively. Discussion: D313Y variation seems to correlate with an atypical, mild late-onset phenotype with predominantly neurologic FD manifestations. Monitoring for CNS/PNS involvement is thus paramount to identify D313Y -positive patients with latent or early-FD pathology, which may qualify for enzyme-replacement therapy or chaperone treatment.